CORRELATIONAL ANALYSIS OF STUDENT VISIBILITY AND PERFORMANCE IN ONLINE LEARNING - Wang, Minjuan (Online Learning, 2004)
This study examines the relationship between student visibility and learning outcomes in a graduate-level online course. Visibility in this study refers to students’ cognitive, social, and emotive presence [1, 2] in various communication settings, such as posts on the discussion board, contributions in live chats, email messages, online profiles, and inputs via any other means of communication. A visibility score is determined for each student, and the Spearman r correlational tests are used to detect any significant correlation between visibility and learning outcomes (grades). In addition, two surveys were distributed to the students at the end of the course: (a) Survey on Self-Perception on Learning Experiences provides a context for understanding student performance; and (b) Survey on Useful Aspects of Socializing Online asks students to rank the importance of eight types of online activities, such as sharing information, solving problems, and making friends. Both surveys probe into students’ perceptions and social context, which often have great impact on students’ online presence.